З історії маєтків Ґалаґанів у селах Сокиринці та Дігтярі: 1760–1810-ті роки - Будзар, М.М. (Сіверщина в історії України, 2021)
У статті розглянуто історію маєтків Галаґанів у селах Сокиринці і Дігтярі того часу, коли ця родина козацько-старшинського
походження активно долучилася до процесу інкорпорації в елітні
структури Російської імперії. Метою розвідки є аналіз стану цих
садибних комплексів у часових межах останньої третини XVIII –
першої чверті XIX століття за письмовими й візуальними джерелами. У статті прослідковується еволюція цих об’єктів у залежності від змін історичних обставин і поведінкових пріоритетів
власників. Авторка осмислює причинно-наслідкові зв’язки між видозмінами у формах облаштування маєтків, традиціях родинного
побуту й процесом адаптації нащадків козацької старшини до манери життя імперської аристократії. Уперше реконструйовано
структуру спадкових помість Ґалаґанів станом на кінець XVIII –
початок XIX ст. й доведено, що така реконструкція надає інформацію про життєдіяльність не лише одного роду, але дворянства
Лівобережної України як регіональної спільноти. A history of Galagan’s family estates in the villages Sokyryntsi and Dihtiari
at that time when the family from Cossack-sergeant background was actively
engaged in incorporation process into the elite structures of the Russian
Empire was considered in the article. Historical and cultural perspective
of the study was applied for that purpose. The aim of the study is to analyze
a state of residential and administrative complexes based on written and visual
sources in time period from the last third of the 18th – to the first quarter
of 19th century. Evolution of the objects, depended on changes of the historical
circumstances and behavior priorities of the owners, is followed in the
article. The author considers cause-and-effect relations between the forms of
estates’ arrangement, traditions of family life and adaptation process of Cossack-
sergeant family to the aristocratic way of life accepted in the Empire. The
study applies comparative analysis of archive sources – namely, texts and visual
sources – to reconstruction of material components of the estates’ complexes
that have not been preserved till nowadays. Consequently, the methods
of attribution and source chronologizing were used for establishing connections
between document’s content and historical events. Simultaneously, the
information defined when the estates began to be used as residential places
in contrast to pure economic purposes. A conclusion regarding what an estate
started to be used as “ancestral home” and when it had gained the features of
palace-park complex was drawn. A reconstructed structure of Galagan’s family
estates in time period from the end of the 18th – to the beginning of the 19th
century was presented for the first time as well as it was proved that such reconstruction
provided information regarding life of all nobility of Left Bank
Ukraine as a regional community in lieu of one single family.